Electroencephalographic study of microalgae DHA omega-3 egg consumption on cognitive function - Mongkol Kaewsutas (2018)
© 2016 Elsevier Ltd This study aimed to determine the effect of microalgae-DHA eggs on functional cortical activity during an attention/inhibition (Go/NoGo) task in young and healthy subjects. In this 8 weeks period subjects were randomly assigned to consume two boiled eggs/day - either normal eggs (DHA = 51.82 mg/day) or microalgae-DHA eggs (DHA = 278 mg/day). They were tested by Emotiv 14-Channels EEG for the relative change in brainwave patterns during Go/NoGo task. Behavioral performance was recorded by Superlab Pro 2.04 program. The influence of consuming microalgae-DHA egg (2 eggs/day) on the activity of the central nervous system during Go/NoGo task can be seen after 4–8 weeks. The study showed that the power of the slow frequency bands increased with significant difference (p < 0.05) between baseline and 8 weeks in those subjects who consumed DHA eggs when performing the Go-task. The increase in slow frequency bands was positively correlated with behavioral performance.